Studi Deskriptif Penggunaan Bahan Ajar IPA dengan Pendekatan STEAM untuk Meningkatkan Literasi Sains Mahasiswa S-2 Pendidikan Dasar - endang, endang widi winarni (Jurnal PGSD, 2023)
This study aims to describe: (1) the implementation of learning using science teaching materials with the STEAM approach and (2) the profile of scientific literacy abilities. This qualitative research was conducted by observing the implementation of learning using science teaching materials with STEAM and students' scientific literacy skills. The research instruments used were observation and tests. The instrument for observing student activities uses the following indicators: (1) Understanding of the material presented in individual teaching materials; (2) The group task of discussing material is strengthened by the results of accessing the learning video link; and (3) the ability of students both individually and in groups to complete projects. The test is used to collect data on students' scientific literacy skills. The data analysis technique used in this research is descriptive analysis. Conclusions (1) The implementation of learning shows that: (a) the achievement of the low category is not found; (b) the achievement of the medium category reached the highest number in the third indicator, namely the ability of students to complete projects both individually and in groups. And (c) the achievement of the high category reached the largest number in the first indicator, namely the understanding of the material presented in individual teaching materials. (2) The profile of students' scientific literacy abilities: (a) the overall teaching material achieved an average score of 84.98; (b) the highest average score on the food digestive system teaching material is 86.43 (c) the lowest average score on the respiratory system teaching material is 83.04.